ALTERNATIVE EXISTENCE OF ART IN “INTERNAL EMIGRATION” IN SLOVAK PART OF CZECHOSLOVAKIA IN YEARS 1977–1989 - BÁTOROVÁ, MÁRIA (Slavia Occidentalis, 2020)
This paper presents a comparison of Slovak and Czech dissidents, the origin of the so-called “silent” dissent, alternative art in Slovakia in the years of normalization, mostly after 1977.